The complete chloroplast genome of Scutellaria meehanioides (Lamiaceae) from Shaanxi Province, China. Issue 6 (3rd June 2021) - Zhang, Caijuan; Xia, Pengguo; Wu, Rui; Mans, Dennis
Abstract: Scutellaria meehanioides C.Y.Wu is a medicinal perennial herb native to China. The complete chloroplast genome sequence of the S. meehanioides was determined and assembled using next generation sequencing methodologies. The complete genome is 152, 484 base pairs (bp) in length and has an overall GC content of 38.4%. The chloroplast genome contains, a large single-copy region (LSC) of 83, 859 bp, small single-copy region (SSC) of 17, 467 bp and a pair of inverted repeats (IRs) of 24, 029 bp. The genome of S. meehanioides contains 133 genes, including 87 protein-coding, 38 tRNA, and 8 rRNA genes. Phylogenetic analysis fully resolved S. meehanioides in a clade with S. orthocalyx. This study provides useful information for future genetic study of S. meehanioides .